2005
DOI: 10.1200/jco.2005.02.7243
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin Pulmonary Toxicity Has a Negative Impact on the Outcome of Patients With Hodgkin's Lymphoma

Abstract: BPT results in a significant decrease in 5-year OS in patients who are treated for HL. Age > or = 40 years seems to add substantially to the risk. In patients who do not die from acute pulmonary toxicity, both OS and PFS seem equal, despite the omission of bleomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
185
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(206 citation statements)
references
References 21 publications
(16 reference statements)
14
185
0
7
Order By: Relevance
“…Specifically protocol ABVD given on schedule, without delay and no growth factor support regardless of the absolute neutrophil count on the day of treatment, is advocated. Of note, however, is the use of stimulatory peptide increases bleomycin induced lung toxicity [53] and [54]. Alternatives are Stanford V and escalated BEACOPP [55] and [56] where encouraging results are offset by a marked increase in both short-and long-term toxicities, including infertility, infectious complications and second malignancies so that there is a relevance to use BEACOPP routinely.…”
Section: Advancedmentioning
confidence: 99%
“…Specifically protocol ABVD given on schedule, without delay and no growth factor support regardless of the absolute neutrophil count on the day of treatment, is advocated. Of note, however, is the use of stimulatory peptide increases bleomycin induced lung toxicity [53] and [54]. Alternatives are Stanford V and escalated BEACOPP [55] and [56] where encouraging results are offset by a marked increase in both short-and long-term toxicities, including infertility, infectious complications and second malignancies so that there is a relevance to use BEACOPP routinely.…”
Section: Advancedmentioning
confidence: 99%
“…As far as bleomycin is concerned, a higher rate of pulmonary toxicity was reported in patients older than 40 years compared to younger patients by the CALGB (38% vs. 22%) and the Mayo Clinic (33% vs. 11). 39,63 A thorough evaluation and surveillance of respiratory function is recommended before and during ABVD chemotherapy in elderly patients, and caution should be used when administering growth factors during bleomycin-containing chemotherapy. Regimens with reduced intensity compared to ABVD are better tolerated; however, this advantage is counterbalanced by the lower remission rate and the higher relapse rate compared to standard dose regimens.…”
Section: Treatment Of Elderly Patientsmentioning
confidence: 99%
“…2,3 Although late deaths have been described, most patients die in the acute inflamma- tory phase. 2 Currently there is no diagnostic tool available to monitor the effects of corticosteroid treatment for BIP or a screening tool to detect early asymptomatic BIP before patients develop pulmonary symptoms and bilateral interstitial infiltrates on chest x-ray or CT scan. Although there is no standard approach, withholding bleomycin, treatment with high-dose corticosteroids, and continuing with a non-bleomycin chemotherapy regimen is the most common management of patients who develop BIP.…”
mentioning
confidence: 99%
“…1 More recently Martin et al reported a BIP incidence rate of 18% when treated with ABVD (25 of 141 patients) and one-quarter of their BIP patients all died from pulmonary toxicity within 9 months of their HD diagnosis. 2 The total dose of administered bleomycin, the age of the patient, and impaired renal function are important risk factors in predicting BIP. 2,3 Although late deaths have been described, most patients die in the acute inflamma- tory phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation